Meta-analysis of comparative effects of mobile app–based digital rehabilitation versus traditional rehabilitation after total knee arthroplasty - Ma, Liang; Liu, Jia-Qiang; Yu, Kun; Tan, Mei-Yun (Frontiers in Physiology, 2026)
ObjectiveThe purpose of this study is to compare the effect of digital rehabilitation based on mobile app and traditional rehabilitation program after total knee arthroplasty.MethodsThe following electronic databases were systematically searched to identify eligible trials: PubMed, EMBASE, Web of Science, the Cochrane Library, Scopus, and CINAHL. The searches were conducted from database inception to 1 December 2025. According to the inclusion and exclusion criteria, literature screening, data extraction and evaluation of its methodological quality were carried out. RevMan5.4 software was used to conduct heterogeneity test and meta-analysis of the included studies, and Cochrane systematic review tool was used to evaluate the literature publication bias. The main outcomes were visual analogue scale (VAS) of pain, “standing walking” timing test, knee function score (KSS), knee range of motion (ROM), and 10-m Walk Test.ResultsThis meta-analysis included 8 studies involving a total of 694 patients. Compared with traditional rehabilitation, the app-based group showed significantly lower pain scores, as assessed by the Visual Analogue Scale (VAS), with a positive mean difference favoring the app-based group (MD = 1.03, 95% CI 0.30 to 1.75; I2 = 0%; P = 0.006). Performance-based functional outcomes favored the app-based group, with significant improvements observed in the Timed Up and Go test (MD = −1.75, 95% CI −2.55 to −0.94; I2 = 19%; P < 0.0001) and the 10-m Walk Test (SMD = 0.47, 95% CI 0.05 to 0.88; I2 = 0%; P = 0.03). Knee range of motion (ROM) was also significantly greater in the app-based rehabilitation group (MD = 6.46°, 95% CI 2.92 to 10.00; I2 = 53%; P = 0.0004). No significant difference was observed in the Knee Society Score (KSS) between groups (P > 0.05). The overall risk of bias among the included studies was moderate, primarily due to unclear allocation concealment and lack of blinding.ConclusionCompared with traditional rehabilitation, mobile app–based digital rehabilitation after total knee arthroplasty was associated with improved pain relief and better performance-based functional outcomes, as well as greater early gains in knee range of motion. No significant difference was observed in composite knee function scores. Given the low to moderate certainty of evidence, app-based rehabilitation may be considered as an adjunct or alternative rehabilitation strategy for selected patients, while further high-quality randomized controlled trials are needed to confirm long-term effectiveness.